CorrespondenceRed rashes to green pastures: sustainable dermatology. (3rd January 2023) - Hussain, Khawar; Kawsar, Anusuya; Roberts, Nerys; Patel, Neil P
Abstract : We performed an anonymous patient survey to find out more about patients' perspectives on the topical treatments they use and recycling their packaging. We provide the results of our pilot study and also summarize key points for future research and development.